Aquatic Developmental Play Program for Children in Early Intervention: A Case Series - Brynn Butzman; Cynthia Lau; Cheryl Vanier (Scholarworks @ WMU, 2022)
Background: Despite limited evidence, aquatic programming has the potential to be an ideal intervention for young children with disabilities because of its unique and dynamic properties. This study explored the impact of an aquatic developmental play program in addressing sensory integration and motor development needs of children with disabilities as well as its impact on parental isolation. Methods: A case series design was used. Children with disabilities under 3 years of age and their parents participated in a 9-week aquatic developmental play program held in the community. Goals were individualized for each participant and monitored using the Goal Attainment Scaling (GAS) method. The Sensory Profile 2, the Developmental Assessment of Young Children-Second Edition (DAYC-2), and a Parent Support Survey were administered before and after the study. Results: Seventy-nine percent of the individual goals were met or exceeded expectations among the 11 participants with categorical changes observed on the Sensory Profile 2 and the DAYC-2. Parental satisfaction with services increased and parental feelings of isolation decreased following the aquatic play program. Conclusion: The results suggest that aquatic programming held in the community may be beneficial not only for the individual needs of children with disabilities but also for the needs of parents.